PARTICULARS OF ASSESSMENT OF QUALITY OF LIFE IN PEDIATRIC AND JUVENILE EPILEPTIC PATIENTS - E. G. Melikian; К. Yu. Mukhin (Эпилепсия и пароксизмальные состояния)
Nowadays, normalization of quality of life is considered to be one of key targets during epilepsy treatment. Given a high prevalence of epilepsy in pediatric and juvenile patients, and particular importance of this age period for the whole further human life, studying of quality of life is a topical issue. However, the first serious studies of quality of life in pediatric and juvenile epileptic patients have only begun in the 90th of the 20th century, i.e., significantly later than those in adult epileptic patients. The insufficient number of scales and methods in pediatrics is linked to objective impediments with definition of quality of life in children and adolescents. This article highlights the main issues of studying quality of life in this age category, shows the particulars of studying quality of life in various age categories and marks out the tasks for future investigations.